Psychosocial Factors Contributing to Critical Thinking in Writing Skills: A Systematic Review of EFL Learners - Amri, Samsul; Sulistiyo, Urip; Sartika, Delita (PPSDP International Journal of Education, 2025)
Critical thinking (CT) in EFL writing is not solely a linguistic ability but a psychosocial process involving regulation, motivation, and social support. This study conducted a PRISMA-guided systematic review (2015–2024) across major databases, screening 364 records and including 20 empirical studies using quantitative, qualitative, and mixed-method designs. Given the heterogeneity of measures, narrative synthesis and vote counting were applied. The findings reveal that key psychosocial contributors to CT in writing include self-regulated learning (SRL) and metacognition, writing self-efficacy, resilience, motivation and grit, teacher autonomy support, feedback, classroom climate, peer collaboration, emotion regulation, and technology-mediated feedback. A cascade model is proposed in which Teacher Autonomy Support and Classroom Climate influence Engagement, which then promotes SRL and Metacognition, leading to Writing Self-Efficacy, Resilience, and Motivation, and ultimately enhancing Critical Thinking in Writing. These relationships are shaped by learners’ anxiety and emotion-regulation capacities, and further strengthened by technology-supported learning environments. The review recommends integrating SRL cycles, autonomy-supportive feedback, peer reasoning routines, and emotion-regulation strategies into EFL writing instruction. Overall, this work offers an evidence-informed framework that connects psychosocial dynamics with reasoning quality in EFL writing and provides a broader conceptual foundation for advancing research in language learning and learner development.